COST-EFFECTIVENESS OF POLYPILL TREATMENT IN HIGH-RISK HYPERTENSIVE SUBJECTS WITH HYPER-CHOLESTEROLAEMIA. (June 2022) - Mazza, Alberto; Bregola, Gianni; Cavazzin, Enrico; Dell'avvocata, Fabio; Giordan, Massimo; Rigatelli, Gianluca; Rosini, Marinella; Bignardi, Bruno; Bragiotto, Antonio; Crino, Tiziano; Chieregato, Gabriella; Fante, Roberto; et al.
Abstract : Objective: Hypertension and hyper-cholesterolaemia is a dangerous combination frequently found in clinical practice. Despite a wide range of medications available for these both conditions, a large proportion of treated patients remain uncontrolled. We aimed to evaluate the cost-effectiveness treatment of a polypill in high-risk hypertensive and hyper-cholesterolemic subjects. Design and method: 46 subjects (mean age 67.4 ± 11.5 years, 69.6% men) treated a with free-combination (FCT) of statins (atorvastatin 63.1%, simvastatin 19.6%, rosuvastatin 8.7%, other 8.6%), renin-angiotensin-system blockers (ramipril 37.1%, perindopril 28.2%, enalapril 11%, zofenopril 4.4%, candesartan 6.5%, valsartan, losartan and telmisartan 4.3%) and calcium-channel blockers (amlodipine 61%, lacidipine and lercanidipine 15.2%, manidipine 6.6%), were switched to once-daily therapy with a polypill containing atorvastatin/perindopril/amlodipine at different doses. The monthly cost for treating patients with FCT and polypill was estimated using pharmacy dispensing records. Blood pressure (BP) and low-density cholesterol (LDL-C) targets values to reach were < 130/80mmHg and < 70 mg/dL, respectively. Categorical variables, were compared using Pearson's chi-squared test. The change of systolic BP (SBP), diastolic BP (DBP), LDL-C levels and the costs of treatments were compared from baseline to the follow-up (FW, 3.5 ± 1.5 months) by the analysis of variance for repeated measures using the Fisher's (F) test. Results: From baseline to the FW, polypill significantly decrease SBP (141.3 ± 10.1 vs. 133.9 ± 10.5, F = 33.8, p < 0.0001), DBP (81.8 ± 5.3 vs. 77.8 ± 4.1, F = 9.3, p < 0.004) and LDL-C values (99.3 ± 31.5 vs. 70.9 ± 18.5, F = 60.6, p < 0.0001), respectively. The BP and LDL-C targets significantly increased from 24.1 to 56.5% (p < 0.05) and 21.7 to 63.1% (p < 0.05), respectively. The average cost of polypill is lower than the FCT one (13.5 ± 0.7 vs. 23.2 ± 5.3 €, p < 0.0001, difference -9.8 ± 5.2 €). No adverse event was observed during the polypill treatment. Conclusions: In high-risk hypertensive and hyper-cholesterolemic subjects, the polypill treatment is cost-effective. National and regional epidemiological data show a prevalence of high-risk hypertensives of about 12%. In perspective, in the local public health-unit 5 Polesana, which gathers about 235 thousand inhabitants, using polypill compared to the FCT could result in annual cost savings of about 3.2 million € (Figure). However, for definite conclusions, further studies including a wider number of subjects in this setting are needed.